2019
DOI: 10.1111/jfpp.14264
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the extrusion process for the development of extruded snacks using peanut, buckwheat, and rice blend

Abstract: Response surface methodology was applied to study the extrusion product of peanut–buckwheat–rice by a twin screw extruder. Effects of peanut–buckwheat flour (PBF) (25%–35%), feed moisture (18%–22%), barrel temperature (120–140°C), and screw speed (15–25 Hz) on the expansion ratio (ER), breaking strength (BS), bulk density (BD), and overall acceptability (OA) of extrusion product were studied based on the central composite rotatable design. Remarkable regression models that explored influences of peanut–buckwhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To find the maximum of the response function, we equate its partial derivatives to a zero and solve the resulting system of equations [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…To find the maximum of the response function, we equate its partial derivatives to a zero and solve the resulting system of equations [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…Previous works demonstrated that pseudocereal grains could not fully replace common cereals due to their lower sectional expansion index (EI) [ 9 ]. Therefore, to obtain products of maximum overall quality, the selection of extrusion parameters and proper feed formulation is still necessary [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because it possesses a characteristic blunt taste [13]. Many studies have focused on improving the nutritional value of rice based products by incorporating soya beans, sorghum, millet, edible insects, and peanut [14] [15] [16]. However, very scanty information is available on bamboo shoot being used to enrich rice flour and consequently rice based products.…”
Section: Introductionmentioning
confidence: 99%